TABLOIDISASI PEMBERITAAN PENJARAHAN RUMAH ANGGOTA DPR DI MEDIA ONLINE KOMPAS.COM - Tarisha Putri Ramadhanti; Nurul Hasfi (Interaksi Online, 2026)
Ideally, media coverage should prioritize public interest; however, it has increasingly shifted toward sensational and entertainment-oriented content. This trend is evident in Kompas.com’s reporting on the looting of a Member of Parliament’s house following the August 2025 demonstrations, which emphasizes emotional aspects, personal life, and trivial elements rather than substantive public issues. Such characteristics reflect tabloidization, understood as the transformation of hard news into infotainment-oriented content that may reduce public sensitivity to important issues. This study aims to identify elements of tabloidization using framing analysis based on Zhongdang Pan and Gerald M. Kosicki, integrated with tabloidization concepts from Carsten Reinemann. The analysis covers syntactic, script, thematic, and rhetorical structures, as well as dimensions of topic, focus, and style. Based on 11 selected articles (August 31–September 14, 2025), the findings show a strong tendency toward tabloidization, particularly through personalization and emotional coverage, indicating a shift toward infotainment practice. Nevertheless, informative aspects remained present although it remains inherently linked to the characteristics of tabloidization.